(untitled) (Al-Mansour Journal, 2023)
Security and protection to internet of Things (IOT) stay a significant test, chiefly because of the large-scale and circulated nature of IOT organizations. Blockchain-based approaches give decentralized security and protection, yet they include huge energy consumption, delays, and computational overhead that isn’t reasonable for most Resource-constrained IOT devices. The Internet of Things (IOT) alludes to the interconnection of savvy devices to gather information. Notwithstanding, an absence of characteristic safety efforts makes IOT defenseless against protection and security dangers. Blockchain abilities like immutability, transparency, auditability, data encryption and operational resilience can assist with addressing most structural inadequacies of IOT. This article presents a review on Blockchain and it’s integrated with different applications and innovations particularly IOT. The goal of this paper is to analyze current research trends on the use of Blockchain related approaches and innovations in an IOT setting. This paper presents the accompanying curiosities, regarding related work: (I) it covers different application areas, coordinating the accessible writing as per this order and (ii)the conventions that utilized in IOT when incorporated with blockchain.